Intravascular ultrasound guided directional atherectomy versus directional atherectomy guided by angiography for the treatment of femoropopliteal in-stent restenosis. (January 2018) - Krishnan, Prakash; Tarricone, Arthur; K-Raman, Purushothaman; Majeed, Farhan; Kapur, Vishal; Gujja, Karthik; Wiley, Jose; Vasquez, Miguel; Lascano, Rheoneil A.; Quiles, Katherine G.; Distin, Tashanne; Fontenelle, Ran; et al.
Background: The aim of this study was to compare 1-year outcomes for patients with femoropopliteal in-stent restenosis using directional atherectomy guided by intravascular ultrasound (IVUS) versus directional atherectomy guided by angiography. Methods and results: This was a retrospective analysis for patients with femoropopliteal in-stent restenosis treated with IVUS-guided directional atherectomy versus directional atherectomy guided by angiography from a single center between March 2012 and February 2016. Clinically driven target lesion revascularization was the primary endpoint and was evaluated through medical chart review as well as phone call follow up. Conclusions: Directional atherectomy guided by IVUS reduces clinically driven target lesion revascularization for patients with femoropopliteal in-stent restenosis.